John Vaughn correspondence - Vaughn, John.
ALS written by Vaughn to S. I. Buckingham [James Silk Buckingham] thanking him for his gift to the American Philosophical Society's library of an account of his experiences in India. Vaughn includes a brief historical sketch of the society and its goals.
Librarian of the American Philosophical Society.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Buckingham, James Silk, -- 1786-1855 -- Correspondence; American Philosophical Society -- History; American Philosophical Society -- Library; Librarians